1979
DOI: 10.1002/maco.19790300905
|View full text |Cite
|
Sign up to set email alerts
|

Initiation and Inhibition of Pitting Corrosion in Alkali Solutions under potentiostatic polarization conditions

Abstract: Initiation and Inhibition of Pitting Corrosion in Alkali Solutions 631 15. M. Brachet und A. Raharinavio: Galvanized steel wire for pre-31. G. Rehm und U. Nurnberger: Stahl u. Eisen 98 (1978) 392-398 32. D. Horstmann: Stahl u. Eisen 88 (1968) 499--507. 33. G. Schmitt und B. Rothmann: Werkstoffe u. Korrosion 28 (1 977) stahlen und Bewehrungsstahlen, Berlin/Miinchen/Dusseldorf (1 9741, 34. W. Fischer und W. Siedlerek: Werkstoff u. Korrosion 28 (1 977) stressed concrete reinforcement, Final Annual Report 1970/71,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

1983
1983
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 31 publications
1
7
0
1
Order By: Relevance
“…gives the same polarization curves as the solution free of aggressive anion. This indicates that ClO 4 anion does not interfere with the mechanism of passivity of the Pb electrode (Abd El Haleem, 1979;Abd El Haleem and Abd El Aal, 1982;Abd El Aal, 1999). A similar finding was reported during the study of the pitting corrosion of lead in NaOH by the author (Abd El Wanees et al, 1991a;.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…gives the same polarization curves as the solution free of aggressive anion. This indicates that ClO 4 anion does not interfere with the mechanism of passivity of the Pb electrode (Abd El Haleem, 1979;Abd El Haleem and Abd El Aal, 1982;Abd El Aal, 1999). A similar finding was reported during the study of the pitting corrosion of lead in NaOH by the author (Abd El Wanees et al, 1991a;.…”
Section: Resultssupporting
confidence: 77%
“…the dissolution current density along the active region increases with an increase in the concentration of ClO 4 -anion. This behaviour indicates that the ClO 4 anion is specifically adsorbed on the metal surface at lower potentials than those expected for the onset of passivity (Abd El Haleem, 1979;Abd El Haleem and Abd El Aal, 1982;Abd El Rehim et al, 1996);…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…In this case, it can be concluded that these low concentrations of chloride are not sufficient to destroy completely the passivating film formed on the metallic surface. Also, the pits formed are not completely active and may undergo repassivation [3][4][5][6][7][8][9][10][11][12][13][14][15]. At higher concentrations of chloride ions the pits formed are assumed to be of the limiting active type.…”
Section: Resultsmentioning
confidence: 99%
“…Pasivní vrstva na povrchu zinku je snadno poškozována přítomností chloridových aniontů, nebo naopak je její tvorba podporována přístupem CO 3 2- [46]. V prostředí 0,5 mol l -1 NaOH byla pozorována směsná skladba korozních produktů na povrchu zinku a zahrnovala ZnO, Zn(OH) 2 , Zn 5 (OH) 6 (CO 3 ) 2 .…”
Section: Vliv Vápenatých Kationtů Na Korozní Chování žáRově Zinkovanéunclassified